Sex-dependent effects of the uncompetitive N-methyl-D-aspartate receptor antagonist REL-1017 in G93A-SOD1 amyotrophic lateral sclerosis mice - Colognesi, Martina; Shkodra, Atea; Gabbia, Daniela; Kawamata, Hibiki; Manfredi, Paolo L.; Manfredi, Giovanni; De Martin, Sara (Frontiers in Neurology, 2024)
The pathogenesis of amyotrophic lateral sclerosis (ALS), a fatal neurodegenerative disease caused by the demise of motor neurons has been linked to excitotoxicity caused by excessive calcium influx via N-Methyl-D-Aspartate Receptors (NMDARs), suggesting that uncompetitive NMDAR antagonism could be a strategy to attenuate motor neuron degeneration. REL-1017, the dextro-isomer of racemic methadone, is a low-affinity uncompetitive NMDAR antagonist.Importantly, in humans REL-1017 has shown excellent tolerability in clinical trials for major depression. Here, we tested if REL-1017 improves the disease phenotypes in the G93A SOD1 mouse, a well-established model of familial ALS, by examining survival and motor functions, as well as the expression of genes and proteins involved in neuroplasticity. We found a sexdependent effect of REL-1017 in G93A SOD1 mice. A delay of ALS symptom onset, assessed as 10%-decrease of body weight (p<0.01 vs control untreated mice) and an extension of lifespan (p<0.001 vs control untreated mice) was observed in male G93A SOD1 mice. Female G93A SOD1 mice treated with REL-1017 showed an improvement of muscle strength (p<0.01 vs control untreated mice). Both males and females treated with REL-1017 showed a decrease in hind limb clasping. Sex-dependent effects of REL-1017 were also detected in molecular markers of neuronal plasticity (PSD95 and SYN1) in the spinal cord and the GluN1 NMDAR subunit in quadricep muscles. In conclusion, this study provides preclinical in vivo evidence supporting the clinical evaluation of REL-1017 in ALS.